How do you solve #2(x-1) + 3= x -3(x+1)#?

1 Answer
Jul 24, 2016

Answer:

I got
#color(white)("XXX")color(purple)(x=-1)#

Explanation:

1. Simplify the Left Side and Right Side Independently of Each Other
#color(red)(2(x-1)+3)=color(blue)(x-3(x+1))#

#color(red)(2x-2+3)=color(blue)(x-3x-3)#

#color(red)(2x+1)=color(blue)(-2x-3)#

2. Move All the Variable (#x#) Terms to One Side and Constant Terms to the Other
Adding #color(green)(2x)# to both sides:
#4xcolor(red)(+1)=color(blue)(-3)#

Subtracting #color(green)(1)# from both sides:
#4x=-4#

3. Reduce the Equation to a Definition of a Single Unit of the Variable (#x#)
Dividing both sides by #color(green)(4)#
#x=-1#